PAKAIAN TRADISIONAL SEDULUR SIKEP DI BOJONEGORO SEBAGAI MEDIUM PEMERTAHANAN BUDAYA DI TENGAH ARUS MODERNISASI - Mayani, Fatikha; Samidi, Samidi; Basundoro, Purnawan (Universitas Padjadjaran, 2026)
This study aims to examine how the Sedulur Sikep community preserves its traditional clothing as part of efforts to preserve local culture amid the tide of modernization. This study uses a qualitative approach with literature study and visual observation methods and descriptive interpretive data analysis. Stuart Hall's theory of representation is used to understand how cultural identity is formed and communicated through clothing symbols, while Clifford Geertz's concept of culture as a system of meaning is used to reveal how the Sedulur Sikep community's clothing practices are part of the construction of social values passed down through generations. The research findings indicate that the traditional attire of the Sedulur Sikep community not only serves as a visual identifier of identity but also carries philosophical meanings related to simplicity, equality, and respect for ancestors. Efforts to preserve traditional Samin clothing include wearing it during important events such as community gatherings, weddings, and other cultural activities. Preservation efforts also involve transmitting values to younger generations and through local government policies that support the use of local cultural symbols in formal settings.